An evaluation of shared reading groups for adults living with dementia: preliminary findings. Issue 2 (20th June 2016) - Longden, Eleanor; Davis, Philip; Carroll, Janine; Billington, Josie; Kinderman, Peter
Abstract : Purpose: – Although there is a growing evidence base for the value of psychosocial and arts-based strategies for enhancing well-being amongst adults living with dementia, relatively little attention has been paid to literature-based interventions. The purpose of this paper is to assess the impact of shared reading (SR) groups, a programme developed and implemented by The Reader Organisation, on quality of life for care home residents with mild/moderate dementia. Design/methodology/approach: – In total, 31 individuals were recruited from four care homes, which were randomly assigned to either reading-waiting groups (three months reading, followed by three months no reading) or waiting-reading groups (three months no reading, followed by three months reading). Quality of life was assessed by the DEMQOL-Proxy and psychopathological symptoms were assessed by the Neuropsychiatric Inventory Questionnaire. Findings: – Compared to the waiting condition, the positive effects of SR on quality of life were demonstrated at the commencement of the reading groups and were maintained once the activity ended. Low levels of baseline symptoms prevented analyses on whether the intervention impacted on the clinical signs of dementia. Research limitations/implications: – Limitations included the small sample and lack of control for confounding variables. Originality/value: – The therapeutic potential of reading groups is discussed as a positive and practical intervention for older adults living with dementia.